Behavior of slender UHPC columns under eccentric loading. (1st November 2018) - Hung, Chung-Chan; Hu, Fuo-Yao; Yen, Cheng-Hao
Highlights: The inclusion of fibers with Vf  = 0.75% restrained concrete spalling and crushing. It also increased the crushing strain of UHPC from 0.0025 to 0.0034. Steel fibers with Vf  = 1.5% compensated a 70% reduction in the confinement steel. UHPC columns with Vf  = 1.5% showed a ductile post-peak behavior. Both the analytical and magnified methods reasonably predicted the moment demand. Abstract: The behavior of slender ultra-high performance concrete (UHPC) columns under eccentric loading was investigated in this study. Eight slender UHPC columns were tested, with the major experimental variables being the amounts of confinement steel and steel fibers. The behavior of the columns was evaluated using various performance measures, including the failure pattern, load–deflection relationship, ductility, steel reinforcement strain, and axial load–moment interaction diagram. Results showed that the inclusion of steel fibers with a volume fraction of 0.75% or more effectively restrained spalling and crushing of the slender UHPC columns. In particular, the inclusion of a 1.5% volume fraction of steel fibers was able to compensate a 70% reduction in the confinement steel while still promoting the ductility of the slender columns under eccentric loading. Furthermore, analytical studies were conducted to estimate the crushing strain of the UHPC material in the outermost fiber of the column section under a combined flexural and axial action. The applicability of an analytical procedure and the current design codes for evaluating the total moment demand of the slender UHPC columns under the influence of the P-Delta effect were also evaluated.